Defining and Treating Older Adults with Acute Myeloid Leukemia Who Are Ineligible for Intensive Therapies - Pettit, Kristen; Odenike, Olatoyosi (Frontiers in Oncology, 2015)
Although acute myeloid leukemia (AML) is primarily a disease of older adults (age ≥60 years), the optimal treatment for older adults remains largely undefined. Intensive chemotherapy is rarely beneficial for frail older adults or those with poor risk disease, but criteria that define fitness and/or appropriateness for intensive chemotherapy remain to be standardized. Evaluation of disease-related and patient-specific factors in the context of clinical decision making has therefore been largely subjective. A uniform approach to identify those patients most likely to benefit from intensive therapies is needed. Here, we review currently available objective measures to define older adults with AML who are ineligible for intensive chemotherapy, and discuss promising investigational approaches.